Comparative Analysis of Prone vs Supine Position in PCNL: A Hospital Based Prospective Study - Shah, Ram Sagar; Mishra, Kartikesh; Shah, Sachidananda; Poudel, Abhishek; Bist, Aayush (Journal of Nepalgunj Medical College, 2025)
Introduction: Percutaneous nephrolithotomy is a standard minimally invasive procedure for managing large or complex renal calculi. While the traditional prone position is commonly used, the supine position has gained attention for its potential benefits in surgical access and outcome. Aims: To compare the intraoperative and postoperative outcomes of prone versus supine percutaneous nephrolithotomy. Methods: A prospective hospital-based study was conducted at Nobel Medical College, Biratnagar, from February 2024 to January 2025. A total of 60 patients with renal stones undergoing percutaneous nephrolothotomy were enrolled and divided into two groups: Group A (prone position) and Group B (supine position), each with 30 patients. Parameters such as operative time (minutes), blood loss (g/dL), stone clearance rate (%), and postoperative complications were recorded and analyzed using SPSS version 16. Results: The mean operative time was shorter in the supine group (80 ± 12 minutes) compared to the prone group (95 ± 15 minutes). Blood loss was lower in the supine group, with fewer patients requiring transfusion. Stone clearance was slightly higher in the prone group (90%) versus the supine group (80%). Postoperative complications, including fever and pain, were comparable between the groups, with no significant differences observed. Conclusion: Both prone and supine percutaneous nephrolithotomy positions are safe and effective. However, the supine position demonstrated advantages in operative time and reduced blood loss, making it a favorable option in selected cases.